2020
DOI: 10.25259/apos_41_2020
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic management of impacted maxillary canines

Abstract: The prevalence of impacted maxillary canines is 2–3%. In Caucasian populations, it is reported to be more palatally displaced than buccally, with the opposite trend seen in Asian populations. At the ages of 9–11 years, the position of the canine germ should be diagnosed, for most children through clinical supervision. In 7–10% of children, the clinical investigation must be supplemented with radiographic investigation, in most cases with intraoral radiographs. About 50% of impacted canines cause root resorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Distalizing the canine away from the incisor root at the earliest is recommended. 10 Age is another determinant for the prognosis of treatment involving the traction of impacted canine into the arch. This case is being highlighted owing to its extremely good outcome despite the presence of 2 factors that could have undermined its prognosis viz: age and a periodontally compromised lateral incisor.…”
Section: Discussionmentioning
confidence: 99%
“…Distalizing the canine away from the incisor root at the earliest is recommended. 10 Age is another determinant for the prognosis of treatment involving the traction of impacted canine into the arch. This case is being highlighted owing to its extremely good outcome despite the presence of 2 factors that could have undermined its prognosis viz: age and a periodontally compromised lateral incisor.…”
Section: Discussionmentioning
confidence: 99%
“…Stabryta cita a varios investigadores como Ericson y Kurol, Bacetti et al, quienes reportan que entre el 65% y 78% de los casos de exodoncias de dientes temporales presentaron erupción espontánea del permanente (Stabryła et al, 2021). Bjerklin et al mencionan que la extracción del canino temporal tiene una mayor tasa de éxito cuando está en el sector 2 o 3 y el ángulo alfa está entre 20° y 30°, (Bjerklin, 2020) además se indica que la exodoncia es exitosa cuando es realizada en la etapa prepubereral (Sharma et al, 2021).…”
Section: Extracción De Dientes Temporalesunclassified
“…Maxillary canines that are embedded in the alveolus, unable to erupt at an appropriate time in the dental arch are considered impacted. 10 The prevalence of impacted maxillary canines is approximately 2%, but varies amongst different ethnicities. 11,12 Studies on orthodontic patients have shown that this condition appears more frequently in females.…”
Section: Introductionmentioning
confidence: 99%